2013
DOI: 10.1093/hmg/ddt131
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymerase ɛ and δ exonuclease domain mutations in endometrial cancer

Abstract: Accurate duplication of DNA prior to cell division is essential to suppress mutagenesis and tumour development. The high fidelity of eukaryotic DNA replication is due to a combination of accurate incorporation of nucleotides into the nascent DNA strand by DNA polymerases, the recognition and removal of mispaired nucleotides (proofreading) by the exonuclease activity of DNA polymerases δ and ɛ, and post-replication surveillance and repair of newly synthesized DNA by the mismatch repair (MMR) apparatus. While th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
306
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 332 publications
(322 citation statements)
references
References 33 publications
12
306
1
3
Order By: Relevance
“…Importantly, our analyses further support previous studies that showed an association of POLE proofreading mutations with younger age and favorable prognosis. 11,29,30 It is noteworthy that in this cohort, the frequency of POLE proofreading mutation was 15%, consistent with its association with high tumor grade 10,11,29 and higher than the 6% frequency detected in unselected low-and intermediate-risk endometrial cancers. 10,11,29,30 In addition, we found that microsatellite instability was associated with a reduced risk of recurrence and distant metastases.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Importantly, our analyses further support previous studies that showed an association of POLE proofreading mutations with younger age and favorable prognosis. 11,29,30 It is noteworthy that in this cohort, the frequency of POLE proofreading mutation was 15%, consistent with its association with high tumor grade 10,11,29 and higher than the 6% frequency detected in unselected low-and intermediate-risk endometrial cancers. 10,11,29,30 In addition, we found that microsatellite instability was associated with a reduced risk of recurrence and distant metastases.…”
Section: Discussionsupporting
confidence: 82%
“…[6][7][8][9][10][11] These alterations have been fitted in the dualistic model of endometrial carcinogenesis discriminating endometrial cancers in the more indolent endometrioid cancers (type 1) and the more aggressive non-endometrioid cancers (type 2). Recently, comprehensive molecular profiling of 373 endometrial cancers suggested that the traditional dualistic model can be improved upon classification of endometrial cancers into four molecular subgroups with a potential prognostic significance: DNA polymerase epsilon (POLE) ultramutated, microsatellite instable hypermutated, copy-number low and copy-number high (serous-like and mostly TP53 mutant).…”
mentioning
confidence: 99%
“…POLE and POLD1 exonuclease domain mutations may occur in the germline, where they cause polymerase proofreading‐associated polyposis – a condition characterized by intestinal polyposis and tumours of the colorectum and uterus, among other organs 7. Somatic POLE exonuclease domain mutations (hereafter simply referred to as POLE mutations) occur in sporadic tumours of the endometrium (7–15% cases) 8, 9, colorectum (1–2%) 10, 11, and, less commonly, in other cancers (although, for reasons that are unclear, somatic POLD1 exonuclease domain mutations are very uncommon). POLE ‐mutant colorectal and endometrial cancers have an excellent prognosis 8, 11, 12, 13, probably owing to a robust antitumour immune response against the multitude of immunogenic neoantigens that they are predicted to harbour 11, 14, 15.…”
Section: Introductionmentioning
confidence: 99%
“…Germline mutations affecting the exonuclease domains of DNA polymerases δ (Polδ) and e (Pole) cause hereditary CRC (19), and somatic changes in the exonuclease domain of Pole were found in sporadic hypermutated CRC and EC (20)(21)(22)(23). Two of these exonuclease domain mutations were modeled in yeast and found to increase mutation rate, supporting their role in the development of hypermutated tumors (19,24).…”
mentioning
confidence: 99%